Optical Coherence Tomography Analysis of Macular Vessel Density and Area of the Foveal Avascular Zone after Single Dose of Anti-Vascular Endothelial Growth Factor Therapy in Eyes with Diabetic Macular Edema - Qureshi, Javeria Ahmed; Ahsan Mukhtar; Asfandyar Khan; Muhammad Asim Mehboob; Muqaddas Noor; Aslam, Farheen (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess the change in macular vessel density and area of foveal avascular zone treated with anti-Vascular Endothelial Growth Factor injection Bevacizumab in patients of diabetic macular edema with Optical Coherence Tomography Analysis. Study Design: Prospective longitudinal study Place and duration of Study: Armed Forces Institute of Ophthalmology Rawalpindi, Pakistan from Jan to Jun 2023. Methods: Patients diagnosed with diabetic macular edema underwent complete eye examination. Optical coherence tomography analysis was done to check macular vessel density of the superficial plexus and area of foveal avascular zone after treatment with single dose of intravitreal anti – Vascular Endothelial Growth Factor Bevacizumab at baseline, two weeks and four weeks respectively. Results: A significant reduction in the macular vessel density (MVD) of the superficial vascular plexus was observed in both the right and left eyes at the 2nd week (right eye: 45.1 ± 0.9%; left eye: 45.0 ± 1.0%) and at the 4th week (right eye: 44.8 ± 0.8%; left eye: 44.5 ± 0.9%).The foveal avascular zone (FAZ) increased significantly post-injection in both eyes. Conclusion: Optical Coherence Tomography Analysis showed significant reduction in vessel density of the superficial vascular plexus and area of foveal avascular zone increased after a single intravitreal anti Vascular Endothelial Growth Factor (anti VEGF) Injection Bevacizumab. It enables us to follow up patients on short term basis who respond to the single dose of anti-VEGF treatment at anatomical level by early detection of changes on OCTA and to ascertain the response to the treatment.